Prevalence and risk factors for silicosis among a large cohort of stone benchtop industry workers - Hoy, Ryan F; Dimitriadis, Christina; Abramson, Michael; Glass, Deborah C; Gwini, StellaMay; Hore-Lacy, Fiona; Jimenez-Martin, Javier; Walker-Bone, Karen; Sim, Malcolm R (Occupational and environmental medicine (London, England), 2023)
ObjectivesHigh silica content artificial stone has been found to be associated with silicosis among stone benchtop industry (SBI) workers. The objectives of this study were to determine the prevalence of and risk factors for silicosis among a large cohort of screened SBI workers, and determine the reliability of respiratory function testing (RFT) and chest x-ray (CXR) as screening tests in this industry.MethodsSubjects were recruited from a health screening programme available to all SBI workers in Victoria, Australia. Workers undertook primary screening, including an International Labour Office (ILO) classified CXR, and subject to prespecified criteria, also underwent secondary screening including high-resolution CT (HRCT) chest and respiratory physician assessment.ResultsAmong 544 SBI workers screened, 95% worked with artificial stone and 86.2% were exposed to dry processing of stone. Seventy-six per cent (414) required secondary screening, among whom 117 (28.2%) were diagnosed with silicosis (median age at diagnosis 42.1 years (IQR 34.8–49.7)), and all were male. In secondary screening, silicosis was associated with longer SBI career duration (12 vs 8 years), older age, lower body mass index and smoking. In those with silicosis, forced vital capacity was below the lower limit of normal in only 14% and diffusion capacity for carbon monoxide in 13%. Thirty-six (39.6%) of those with simple silicosis on chest HRCT had an ILO category 0 CXR.ConclusionScreening this large cohort of SBI workers identified exposure to dry processing of stone was common and the prevalence of silicosis was high. Compared with HRCT chest, CXR and RFTs had limited value in screening this high-risk population.